A Secure and Intelligent Healthcare Chatbot Using Blockchain And AI - G DEEPTHI SARANYA; Mrs. A DURGA BHANVANI; Dr G VISHNU MURTHY (Utilitas Mathematica, 2025)
In recent years, the healthcare industry has increasingly adopted digital solutions to improve efficiency, accessibility, and patient experience. However, the rapid digitization of health information raises critical concerns around data privacy, security, and unautho- rized access. This project introduces a comprehensive web-based system that securely manages and stores electronic health records using Ethereum blockchain technology. Developed using Python Django, HTML, CSS, JavaScript, Bootstrap, and MySQL, the system ensures that all medical data is handled in a secure, transparent, and decentralized manner. The core of this system is built upon blockchain technology powered by Ethereum and tested on the Ganache local blockchain environment, which enables tamper-proof storage and retrieval of sensitive patient information through smart contracts. The application comprises three main user portals: Admin, Doctor, and Patient. The Admin can register, manage, and monitor both doctors and patients while reviewing user feedback to ensure the smooth operation of the platform. Doctors can manage their profiles, handle appointment scheduling, and communicate di- rectly with patients through a built-in messaging system. Patients can explore doctor profiles, book appointments, view their medical history, and interact with doctors in real-time. One of the key highlights of this system is the integration of a healthcare chatbot using the Perplexity API, which assists patients by responding to common medical queries, thus improving accessibility and reducing dependence on direct consultations for preliminary concerns. Blockchain plays a vital role by providing a secure environment for health record storage. Once a record is uploaded, it is hashed and stored immutably on the Ethereum blockchain using smart contracts, ensuring that the data cannot be altered or deleted by any unau- thorized party. This approach significantly strengthens the trust, integrity, and confidentiality of patient records. By combining modern web technologies, artificial intel- ligence, and blockchain, this project demonstrates an efficient, user-friendly, and highly secure solution for managing digital health records in a scalable and future- ready manner.